Certainty of Subject Matter in the Development of Intellectual Property: Please Sir I Want Some More! - WEI, George S. S. (Institutional Knowledge at Singapore Management University, 2009)
This article discusses the need for greater certainty of subject-matter in developing guiding principles in intellectual property rights. It begins by noting the importance of certainty of subject-matter in property law in general and argues that certainty as to the scope of what is protected by intellectual property law is no less important especially with the strengthening of the rights conferred (particularly in copyright). It examines briefly the need for certainty of subject-matter in the context of registered trade marks and patent law before moving into a discussion of copyright and in particular the position of names and titles. It argues for greater caution in the use of competition driven mantra such as "reaping where you have not sown" in developing property based rights and for copyright law to make conscious attempts to apply with greater clarity and rigour the expression/idea or facts dichotomy.